2020
DOI: 10.1007/s40259-020-00418-x
|View full text |Cite|
|
Sign up to set email alerts
|

MYL1501D Insulin Glargine: A Review in Diabetes Mellitus

Abstract: Subcutaneous MYL1501D insulin glargine 100 U/mL (hereafter referred to as MYL1501D insulin glargine) [Semglee ® ] is a long-acting human insulin analogue approved as a biosimilar of insulin glargine 100 U/mL (hereafter referred to as reference insulin glargine 100 U/mL) [Lantus ® ] in various countries, including those of the EU for the treatment of diabetes mellitus in patients aged ≥ 2 years, as well as Japan for diabetes where insulin therapy is indicated. MYL1501D insulin glargine has similar physicochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Biosimilar insulin glargine, the first long-acting insulin analogue biosimilar, has been shown to have similar effectiveness and safety to the originator in a number of studies including those conducted in Japan (68)(69)(70)(71)(72). However, there can be concerns with the extent of price reductions versus originators in practice as seen in the United Kingdom, which may impact on future use in practice (73)(74)(75)(76).…”
mentioning
confidence: 99%
“…Biosimilar insulin glargine, the first long-acting insulin analogue biosimilar, has been shown to have similar effectiveness and safety to the originator in a number of studies including those conducted in Japan (68)(69)(70)(71)(72). However, there can be concerns with the extent of price reductions versus originators in practice as seen in the United Kingdom, which may impact on future use in practice (73)(74)(75)(76).…”
mentioning
confidence: 99%
“…Biosimilars are a potential way forward to reduce the cost of long-acting insulin analogues building on the appreciable price reductions seen with biosimilars to treat rheumatoid arthritis [52][53][54][55][56]. In addition, a number of published studies have now demonstrated similar effectiveness and safety between the originator and biosimilar long-acting insulin analogues [57][58][59][60][61]. However, potential savings from biosimilar insulin glargine can be limited in practice, potentially accentuated by the dominance of three companies currently controlling 96% of the global insulin market by volume and 99% by value discouraging competition [36,46].…”
Section: Introductionmentioning
confidence: 99%
“…Participants from INSTRIDE 1 who completed 52 weeks of reference insulin glargine treatment were randomized 1:1 to the reference sequence (n = 63; insulin glargine for 36 weeks) or to the treatment-switching sequence (n = 64; MYL-1501D [weeks 0-12], insulin glargine [weeks [12][13][14][15][16][17][18][19][20][21][22][23][24], MYL-1501D [weeks [24][25][26][27][28][29][30][31][32][33][34][35][36]). The primary efficacy endpoint used to show equivalence between the two treatment sequences was a change in HbA1c from baseline to week 36.…”
Section: Methodsmentioning
confidence: 99%
“…It took Mylan/Biocon quite a while to get this approval, at least in part due to a lawsuit Sanofi has filed against Mylan/ Biocon alleging infringement of its patents and also due to a number of quality issues with the insulin manufacturing plant that the FDA raised repeatedly to BioCon; these were solved NEW INSULINS, BIOSIMILARS, AND INSULIN THERAPY S-65 more recently (https://www.centerforbiosimilars.com/news/ biocons-malaysia-insulin-plant-is-okd-by-fda). The properties of MYL-1501D were presented in detail in a recent review of this drug (32). Semglee has already acquired approvals in more than 40 countries, including Europe, Australia, Japan, and South Korea, and is on the market in a number of these.…”
Section: Semglee (Mylan Myl-1501)mentioning
confidence: 99%